Augmented reality-based biology practicum guide on viruses to enhance digital literacy - Herlina, Meti; Syahfitri, Jayanti (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2026)
Digital literacy is essential in science education, where abstract concepts benefit from technology-supported visualization. However, conventional practicum materials frequently offer limited opportunities to develop these skills. This study examined the effectiveness of an Augmented Reality (AR)-based biology practicum guide on virus-related topics in improving students’ digital literacy. Using a quasi-experimental, non-equivalent control group design, the study involved 50 tenth-grade students at SMA Negeri 3 Rejang Lebong, Indonesia, split equally into an experimental group (AR guide, N = 25 and a control group (conventional material, N = 25). Data collected using a digital literacy questionnaire (technical, cognitive, and social-emotional dimensions) were analyzed using a t-test and N-Gain score (0.62 / 61.7%; effective) compared to the control group (0.28 / 28%; ineffective), with a very large effect size analysis (Cohen’s d = 2.76). These findings indicate that the AR-based biology practicum guide effectively enhances students’ digital literacy by supporting technology operation skills, critical information processing, and responsible digital engagement. Therefore, integrating AR into biology practicum activities represents a promising strategy for advancing 21st-century learning in secondary education.